Is there really an eccentric action of the hamstrings during the swing phase of high-speed running? Part II: Implications for exercise - Van Hooren, B.; Bosch, F. (Journal of Sports Sciences, 2017)
We have previously argued that there may actually be no significant eccentric, but rather predominantly an isometric action of the hamstring muscle fibres during the swing phase of high-speed running when the attachment points of the hamstrings are moving apart. Based on this we suggested that isometric rather than eccentric exercises are a more specific way of conditioning the hamstrings for high-speed running. In this review we argue that some of the presumed beneficial adaptations following eccentric training may actually not be related to the eccentric muscle fibre action, but to other factors such as exercise intensity. Furthermore, we discuss several disadvantages associated with commonly used eccentric hamstring exercises. Subsequently, we argue that high-intensity isometric exercises in which the series elastic element stretches and recoils may be equally or even more effective at conditioning the hamstrings for high-speed running, since they also avoid some of the negative side effects associated with eccentric training. We provide several criteria that exercises should fulfil to effectively condition the hamstrings for high-speed running. Adherence to these criteria will guarantee specificity with regards to hamstrings functioning during running. Practical examples of isometric exercises that likely meet several criteria are provided.